1062. Analysis of Resistance to Oral Standard of Care Antibiotics for Urinary Tract Infections Caused By Escherichia coli and Staphylococcus saprophyticus Collected Worldwide between 2019-2020. (4th December 2021) - Arends, S J Ryan; Butler, Deborah; Scangarella-Oman, Nicole; Paustian, Lindsey; Streit, Jennifer M; Mendes, Rodrigo E
Abstract: Background: Gepotidacin (GSK2140944) is a novel triazaacenaphthylene bacterial type II topoisomerase inhibitor under development for the treatment of gonorrhea and uncomplicated urinary tract infections (UTI). This study reports on the in vitro activity of gepotidacin and other oral antibiotics when tested against contemporary Escherichia coli and Staphylococcus saprophyticus clinical isolates collected from patients with UTIs for a gepotidacin uUTI global surveillance study as a part of the SENTRY Antimicrobial Surveillance Program. Methods: A total of 3, 562 E. coli and 344 S. saprophyticus isolates were collected between 2019 and 2020 from 92 medical centers located in 25 countries. Most isolates (68%) tested were cultured from urine specimens collected from patients seen in ambulatory, emergency, family practice, and outpatient medical services. Bacterial identifications were confirmed by MALDI-TOF. Isolates were tested for susceptibility by CLSI methods at a central laboratory (JMI Laboratories). MIC results for oral antibiotics licensed for the treatment of uUTI and drug-resistant subsets were interpreted per CLSI guidelines. Results: Gepotidacin (MIC50/90, 2/2 mg/L) displayed good activity against 3, 562 E. coli isolates, with 98.0% of all observed gepotidacin MICs ≤4 mg/L (Table). Susceptibility (S) rates for the other oral agents tested against these isolates were: amoxicillin-clavulanate (79.6% S), ampicillin (45.6% S), ciprofloxacin (72.5%S), fosfomycin (99.0% S), mecillinam (94.1%S), nitrofurantoin (97.3% S), and trimethoprim-sulfamethoxazole (68.2% S). When tested against the drug-resistant subsets, gepotidacin maintained similar MIC50/90 values (2/4 mg/L), except against isolates resistant to fosfomycin (2/8 mg/L). Against S. saprophyticus isolates, gepotidacin (MIC50/90, 0.06/0.12 mg/L) inhibited all isolates at ≤0.25 mg/L. Most oral agents showed S results of >97% against S. saprophyticus isolates, except for penicillin (3.5%S). Conclusion: Gepotidacin demonstrated potent in vitro activity against contemporary E. coli and S. saprophyticus urine isolates. This activity was largely unaffected among isolates demonstrating drug-resistance to other oral standard of care antibiotics. Table Disclosures: S J Ryan Arends, PhD, AbbVie (formerly Allergan ) (Research Grant or Support)GlaxoSmithKline, LLC (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Nabriva Therapeutics (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Deborah Butler, n/a, GlaxoSmithKline, LLC (Employee) Nicole Scangarella-Oman, MS, GlaxoSmithKline, LLC (Employee) Lindsey Paustian, BS (ASCP ), GlaxoSmithKline, LLC (Research Grant or Support) Jennifer M. Streit, BS, GlaxoSmithKline, LLC (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Rodrigo E. Mendes, PhD, AbbVie (Research Grant or Support)AbbVie (formerly Allergan ) (Research Grant or Support)Cipla Therapeutics (Research Grant or Support)Cipla USA Inc. (Research Grant or Support)ContraFect Corporation (Research Grant or Support)GlaxoSmithKline, LLC (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Nabriva Therapeutics (Research Grant or Support)Pfizer, Inc. (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support)